Absence of thrombocytopaenia and/or microangiopathic haemolytic anaemia does not reliably exclude recurrence of atypical haemolytic uraemic syndrome after kidney transplantation. (February 2017) - Krishnan, Anoushka R; Siva, Brian; Chakera, Aron; Wong, Germaine; Wong, Daniel; Lim, Wai H
Abstract: A 54‐year‐old man was diagnosed with atypical haemolytic uraemic syndrome (aHUS) with confirmed complement H mutation in 2012, requiring ongoing dialysis. He was commenced on eculizumab in 2014 once the pharmaceutical board approved this drug. After 4 months, he received a live unrelated donor renal transplant from his wife and continued eculizumab post‐transplant. Three months later, there was a rise in his creatinine with no laboratory features of haemolysis and a kidney biopsy confirmed rejection, which was treated with increased immunosuppression. After completing 12 months of treatment with eculizumab, he opted for close monitoring rather than continuation with therapy. Five months post‐cessation of the drug, there was a rise in creatinine, and once again, haematological parameters remained within reference range; however, his kidney biopsy showed features consistent with recurrence of aHUS; hence, eculizumab was recommenced with good effect. While there was no evidence of haemolysis, there was a gradual rise in LDH level and a drop in platelet count, although the parameters remained within the normal range. This suggests that aHUS can recur in the allograft in the absence of haematological abnormalities. Clinicians should have a low threshold for allograft biopsy if haematological parameters are not just outside the reference range, but possibly also if there are changes of at least >25% from baseline in platelet count and LDH levels, particularly in those patients who are no longer eligible for eculizumab.